Job Characteristics, Work-Family Conflict, and Psychological Well-being in Construction Industry Employees - Nugroho, Agung Budiawan (Universitas Pendidikan Nasional, 2023)
Indonesia's construction industry has experienced remarkable growth over the past decade, as evidenced by statistical data from 2010 to 2019. The number of companies focused on construction has surged in tandem with Indonesia's economic growth. However, this rapid growth has led to a significant discrepancy between the increasing number of staff and available companies. Such an imbalance places immense pressure on construction staff, straining their workloads and overall job satisfaction. To address this issue, a comprehensive research study was conducted employing a combination of field research and literature reviews. The research involved direct visits to the study site to gather primary data from respondents. Primary data collection methods included observations and the use of questionnaires, which probed various variables relevant to the study. Furthermore, extensive literature reviews were conducted, drawing insights from journals, articles, textbooks, and relevant government regulations. The primary objective of this research was to investigate the relationship between workload, work distress, sleep problems, and job satisfaction among employees within the construction industry. The study aimed to identify potential avenues for enhancing employee job performance by mitigating familial and sleep-related challenges. The research focused on employees working within multinational and international contractor branches, as the exact population figures were unavailable, necessitating a nonprobability sampling approach. The research employed quantitative analysis, specifically structural equation modeling (SEM), to examine the intricate connections between work-related factors and their impact on employees' well-being and job satisfaction. The findings of the study revealed both direct and indirect influences of work and family dynamics on job-related issues within the private sector. Notably, companies in the construction industry experienced heightened work pressure, attributed to their higher workload, yet also exhibited greater support from regulatory and business sectors. This research underscores the significance of distinguishing between different sectors when exploring the interplay between work and family dynamics. By shedding light on the unique challenges faced by the construction industry, this study contributes to the existing body of work-family literature, emphasizing the need for tailored approaches when analyzing work-family relationships in distinct sectors.